Teori Belajar Behaviorisme dalam Pembiasaan Shalat Jum’at pada Anak Usia Dini - Al ‘Ilmah, Mumtazah; Larasingtyas, Niken; Noorhidayati, Salamah; Ridho, Muhammad; Junaidi, Mahbub (Kuttab: Jurnal Ilmu Pendidikan Islam, 2024)
Early childhood is a golden period of development. Early childhood education must be carried out properly and optimally, includes Jum’at prayer education. Parents must understand how to get children do Jum’at prayers. Through behavioral learning theory, parents can easily condition the habit of Jum’at prayers. This study aims to explore in depth how behavioral learning theory influences the habit of Jum’at prayers in early childhood. This study uses a descriptive qualitative design through interview, observation and documentation methods. This study is a behavioral learning theory through stimulus and response can effectively train children to perform Jum’at prayers. This learning theory can also train children's responsibility, discipline, readiness to do something, love for religion and invite children to like to give alms.